Analysis of Surface Roughness Parameters of Copper Alloy Ring Synchronizer Outer Components Fabricated by CNC Turning on the Okuma 2SP-150H Lathe - Abbas, Aries; Saputra, Alfian Ady (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
The change of insert chips in the CNC Turning Surface Finishing process has led to mismatched turning parameters and a deterioration in the surface roughness quality of the Ring Synchronizer Outer. As a result, it is necessary to optimize the cutting parameters to maintain surface roughness quality and improve process time efficiency. A process capability index analysis (Cp and Cpk) was conducted to ensure process stability under mass production conditions. This study adopts a quantitative and experimental research method. The research activities include calculating three CNC Turning Surface Finishing parameters, conducting CNC Turning process trials, measuring surface roughness, and calculating the Cp and Cpk values. The independent variable in this study is the feed rate (mm/rev), while the dependent variable is surface roughness, represented by the Ra (average roughness) value in micrometers (μm). The results of the CNC Turning Surface Finishing tests for the three parameters are as follows: Parameter 1 (n = 2000 rpm and f = 0.04 mm/rev) produced a Ra value of 0.284 μm (very smooth), with a cutting time of 2.44 seconds, Cp = 27.59, and Cpk = 4.90. Parameter 2 (n = 2000 rpm and f = 0.07 mm/rev) resulted in a Ra of 0.547 μm (smoother), cutting time of 1.39 seconds, Cp = 20.51, and Cpk = 7.01. Parameter 3 (n = 2000 rpm and f = 0.10 mm/rev) achieved a Ra of 0.803 μm (smooth and within standard), with a cutting time of 0.975 seconds, Cp = 20.77, and Cpk = 10.29. Based on these results, it can be concluded that Parameter 3 is the most suitable and time-efficient configuration.